France resurgent - Gouin, Félix; Morandat, Léon; Guigui, Albert; Philip, André; Lévy, Louis; Grenier, Fernand; Hauck, Henry (London: International Publishing Company, 1943)
"Contributors: Félix Gouin, Léon Morandat, Albert Guigui, André Philip, Louis Levy, Fernand Grenier et Henry Hauck ; preface: Socialist Vanguard Group Bibliotheek Camille Huysmans"